Evaluation of an antigen-antibody “combination” enzyme linked immunosorbent assay for diagnosis - (:unkn) unknown (My University, 2014)
Background Development of “combination” assays detecting in parallel, within a single test, Hepatitis C Virus (HCV) antigens and antibodies, not only reduces the window period in HCV-infection but also costs. Reduction of costs is important for developing countries where money and personal resources are limited. Methods We compared the Monolisa® HCV Antigen-Antibody Ultra (Bio-Rad Laboratories Limited, Marnes La Coquette, France) with the AXSYM HCV version 3.0 (Abbot Diagnostics, Germany)-the latter assay detecting only antibodies to HCV. Seventy three HCV-PCR positive and negative samples were tested. Results Although the two assays showed comparable results, two samples from a bone marrow transplant (BMT) patient of viral loads 7.8 × 105 and 8.9 × 106 IU/mL could not be detected by the Monolisa® HCV Antigen-Antibody Ultra assay. Failure to detect the two samples with viral loads considered above threshold of detection for antigen proteins suggested a lack of sensitivity by this assay to discover viral capsid protein in patient samples. Genotyping of these samples revealed genotype 1b, a HCV-subtype which is widespread and should thus be easily detected. Conclusion We conclude that although this assay depicts high sensitivity and specificity in detecting antibodies to HCV, it seems not to add further benefit in our study population to detect HCV infections by enhanced sensitivity due the potential contingency to trace viral capsid antigens.
Keywords: Ag-Ab Combination assay; Hepatitis C Virus; ELISA; Monolisa HCV Ag-Ab Ultra